2017
DOI: 10.21873/anticanres.12144
|View full text |Cite
|
Sign up to set email alerts
|

Control of Nausea Based on Risk Analysis in Patients with Esophageal and Gastric Cancer Who Received Cisplatin-based Chemotherapy

Abstract: Cisplatin is commonly used for esophageal and gastric cancer, however, the agent has high emetic risk, classified as highly emetic chemotherapy. Ohtsu et al. demonstrated in patients with advanced gastric cancer that 5-fluorouracil (5-FU) plus cisplatin led to a significantly higher tumor response rate and longer median progression-free survival but not overall survival as compared with 5-FU alone (1). Koizumi et al. also reported in phase 3 study comparing the effect of S-1 alone and its combination with cisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Furthermore, In a systematic review carried out by Mosa et al, it was reported that the risk of CINV is reduced by 4% with the increase of age by 1 year (Mosa, Hossain, Lavoie, & Yoo, 2020). Regarding gender, in many studies, women persistently had a higher risk of CINV than men (Fujii et al, 2017;Mosa et al, 2020;Sekine et al, 2013;Takemoto et al, 2017;Tamura et al, 2015;Tsuji et al, 2017;Uchida et al, 2017).…”
Section: Logistic Regression Of Chemotherapy-induced Nausea and Vomit...mentioning
confidence: 99%
“…Furthermore, In a systematic review carried out by Mosa et al, it was reported that the risk of CINV is reduced by 4% with the increase of age by 1 year (Mosa, Hossain, Lavoie, & Yoo, 2020). Regarding gender, in many studies, women persistently had a higher risk of CINV than men (Fujii et al, 2017;Mosa et al, 2020;Sekine et al, 2013;Takemoto et al, 2017;Tamura et al, 2015;Tsuji et al, 2017;Uchida et al, 2017).…”
Section: Logistic Regression Of Chemotherapy-induced Nausea and Vomit...mentioning
confidence: 99%
“…Persistent CIN can lead to dehydration, nutritional deficits, decrements in quality of life, and even discontinuation of treatment. 4 Based on findings from cross-sectional studies, risk factors for CIN include age older than 60 years, [5][6][7] female gender, [6][7][8] lower functional status, 3 highly emetogenic chemotherapy regimens, 3,5,6,8 and higher serum albumin levels. 5 Although the occurrence of CIN during the first cycle of chemotherapy is a risk factor in future cycles, 4 only 4 longitudinal studies have evaluated for changes in the occurrence of CIN over time.…”
mentioning
confidence: 99%
“…Chemotherapy-induced nausea and vomiting (CINV) is one of the most common and feared side effects of cancer treatment [1, 2]. Despite use of modern prophylactic anti-emetic regimens according to international guidelines [3], up to 33% of patients treated with highly- or moderately-emetogenic chemotherapy experience one or more episodes of emesis and up to 62% experience nausea [46]. Patients experiencing CINV may be less likely to complete their prescribed chemotherapy regimen due to the significant impact of CINV on quality of life and activities of daily living [7, 8].…”
mentioning
confidence: 99%